Requirements of Aerial Applicators in Florida - Frederick M. Fishel (EDIS)
This guide explains the requirements for applying pesticides, fertilizer and seed with an aircraft in Florida. This document is PI-58, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2005.